FTO (Fluorine-Doped Tin Oxide) Conductive Transparent Glassware Manufacturing For Organic Compound Based Solar Cell Kits - Riski Titian Ginting; Leow Wai Zhe; Thomson Purba (ETAPs (Journal Electronics, Telecommunication, Electrical, and Physics Science, 2021)
Practical activities based on the latest science are rarely carried out because they are constrained by expensive equipment, one of which is solar cell technology. The use of conductive glass has become an interesting topic in recent technology. This technology can be implemented in photovoltaic cells (solar cells) and organic lightemitting diodes (OLED), which are very close to our current needs to face the energy crisis. This study aims to develop practical activities in a chemistry. laboratory for the manufacture of fluorine-doped Tin Oxide (FTO)-based surface conductive glass. This research was conducted using educational design research methods using the framework of the Model of Educational Reconstruction (MER). This research produces Transparent Conductive Glass FTO (Fluorine-doped Tin Oxide) with spray deposition technique / Spray Pyrolysis using a Bunsen burner, the result of optimization of some surface conductive glass with sheet resistance of about 1 – 10 kΩ. These results were obtained by applying ten times of SnO2.F deposition on the glass, three times of spraying, and a heating time of about five minutes at a temperature of 250 – 300 °C. This procedure is obtained using a simple laboratory apparatus such as a Bunsen burner, which is available in the Basic chemistry laboratory for applying NOST (Nature of Science and Technology).